'I think it's boring if you now only speak English': enhancing learner investment in EFL learning through the use of plurilingual tasks. Issue 1 (1st January 2022) - Cutrim Schmid, Euline
ABSTRACT: Purpose: This paper presents findings of a classroom-based research project that investigated the use of plurilingual tasks in the English as a foreign language (EFL) teaching context. The project aimed at examining a) the impact of the use of plurilingual tasks on language learning processes and learners' identity construction and b) the pedagogical gaps that need to be addressed in language teacher education. This paper focuses specifically on the first research question. Design/methodology: The project was carried out in the form of five case studies conducted in four primary schools and one secondary school in Germany. Research data were collected via a variety of ethnographic research instruments namely classroom observations and field notes, video recording of school lessons, in-depth interviews with teachers, teachers' reflective journals, anonymous questionnaires, and learner focus group interviews. Research findings: Drawing upon Darvin and Norton's (2015) concept of investment, the paper discusses research findings indicating that the use of plurilingual tasks had a positive impact on the EFL learners' investment in language learning activities. Originality/Value: The main implication that can be drawn from the findings is that the effective integration of plurilingual-inspired pedagogies in the foreign language classroom does not involve necessarily a drastic reformulation of learning goals and teaching procedures, but mainly a change in teachers' attitudes towards plurilingualism in the classroom.